2018
DOI: 10.1016/j.foodres.2017.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Some physical and functional properties of finger millet (Eleusine coracana) obtained in sub-Saharan Africa

Abstract: The study determined the physical properties of finger millet (FM) (Eluesine coracana) grains and the functional properties of FM flour. Physical properties such as colour attributes, sample weight, bulk density, true density, porosity, surface area, sample volume, aspect ratio, sphericity, dimensional properties and moisture content of grain cultivars were determined. Water absorption capacity (WAC), bulk density (BD), dispersibility, viscosity and micro-structure of FM flours were also evaluated. Data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 40 publications
9
63
3
Order By: Relevance
“…The results are in a similar range with the previous studies that stated the average length, width and height of pearl millet grain was 2.8 to 3.7 mm, 1.7 to 3.3 mm and 1.4 to 2.1 mm respectively [34] , [35]. Similarly, for finger millet grain, values were 1.72± 0.16, 1.7± 0.13, 1.61± 0.19, 1.675± 0.33 respectively, which are close to the range reported by Ramashia et al [36]. The 1000 grain weight was 10.58±0.29 gm and 3 ±0.06 gm respectively for pearl millet and finger millet kernels.…”
Section: A Physical Propertiessupporting
confidence: 86%
“…The results are in a similar range with the previous studies that stated the average length, width and height of pearl millet grain was 2.8 to 3.7 mm, 1.7 to 3.3 mm and 1.4 to 2.1 mm respectively [34] , [35]. Similarly, for finger millet grain, values were 1.72± 0.16, 1.7± 0.13, 1.61± 0.19, 1.675± 0.33 respectively, which are close to the range reported by Ramashia et al [36]. The 1000 grain weight was 10.58±0.29 gm and 3 ±0.06 gm respectively for pearl millet and finger millet kernels.…”
Section: A Physical Propertiessupporting
confidence: 86%
“…Higher values for boiled and roasted flours WAC indicated that they could be included into aqueous food formulations in food processing that would involve preparation of dough such as baking. For instance, some reports (Aprianita et al, 2014;Ramashia et al, 2017) indicated that flour with high WAC encouraged initial softness in bread, while decreasing unnecessary firmness. It also enhanced smoothness and viscosity of the baked product.…”
Section: Effect Of Processing Methods On Functional Properties Of Tammentioning
confidence: 99%
“…According to the FAO, the traditional food processing methods, such as decortications, milling, germination, fermentation, malting, and roasting of millets are recommended in order to prevent their antinutritional properties and improve their edible qualities. Functional properties, such as water and oil holding capacity, viscosity, foaming activity, bulk density, and swelling power of millets are the fundamental physicochemical properties that reveal the intricate relations between the structure, molecular components and composition and physicochemical properties of food components (Ramashia, Gwata, Meddows‐Taylor, Anyasi, & Jideani, ). Table shows the content of proximate composition of different varieties of millets.…”
Section: Introductionmentioning
confidence: 99%
“…Functional properties, such as water and oil holding capacity, viscosity, foaming activity, bulk density, and swelling power of millets are the fundamental physicochemical properties that reveal the intricate relations between the structure, molecular components and composition and physicochemical properties of food components (Ramashia, Gwata, Meddows-Taylor, Anyasi, & Jideani, 2017). Table 1 shows the content of proximate composition of different varieties of millets.…”
mentioning
confidence: 99%